Transforming U.S. Army Supply Chains: Strategies for Management Innovation - Parlier, Greg H (Business Expert Press, 2012)
This text offers a practical approach for understanding the U.S. Army’s extremely complex global logistics system, widely acknowledged as one of the largest in the world. The focus is on inventory management policy where prescriptions are illuminated through the prism of an enterprise supply chain analysis. Although Army aviation logistics examples are emphasized throughout, the fundamental issues and potential solutions are broadly applicable to other large-scale military and industrial supply chains as well. Following a summary of recent trends for background and context, a multistage conceptual model of the logistics structure is presented to segment and guide the effort. This multistage model is used to systematically analyze major organizational components of the supply chain, diagnose structural, disorders and prescribe solutions. Integration challenges are addressed using cost-benefit perspectives, which incorporate supply chain objectives of efficiency, resilience, and effectiveness. The design and evaluation section proposes an “analytical architecture” consisting of four complementary modeling approaches, collectively referred to as “dynamic strategic logistics planning,” to enable a coordinated, enterprise approach for U.S. Army Logistics Transformation. An organizational construct is presented for an “engine for innovation” to accelerate and sustain continual improvement for Army logistics and supply chain management—a “Center for Innovation in Logistics Systems.” Finally, strategic management challenges associated with enterprise integration and transformational change are addressed: organizational design; management information and decision support systems; strategic alignment for a learning organization; and workforce considerations including human capital investment needs. The text concludes with a relevant historical vignette and closes with a summary of expected benefits.